Correcting mistakes: Cognitive dissonance and political attitudes in Sweden and the United States - Mikael Elinder (Uppsala University, Department of Economics, 2009)
Cognitive dissonance theory predicts that the act of voting makes people more positive toward the party or candidate they have voted for. Following Mullainathan and Washington (2009), I test this prediction by using exogenous variation in turnout provided by the voting age restriction. I improve on previous studies by investigating political attitudes, measured just before elections, when they are highly predictive of voting. In contrast to earlier studies I find no effect of voting on political attitudes. This result holds for a variety of political attitudes and for both Sweden and the United States.
urn:nbn:se:uu:diva-106713
Keywords: B59; C21; D72; 330; Cognitive dissonance; Voting; Elections; Political Attitudes; Wahlverhalten; Meinung; Psychologie; Kognition; Schweden; USA